2010
DOI: 10.1177/0091270009355161
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation in Metabolizing Enzyme and Transporter Genes: Comprehensive Assessment in 3 Major East Asian Subpopulations With Comparison to Caucasians and Africans

Abstract: The advent of high-throughput technologies has proven valuable in the assessment of genetic differences and their effects on drug activation, metabolism, disposition, and transport. However, most studies to date have focused on a small number of genes or few alleles, some of which are rare and therefore observed infrequently or lacked rigorous ethnic characterization, thus reducing the ability to extrapolate within and among populations. In this study, the authors comprehensively assessed the allele frequencie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
107
2
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 197 publications
(125 citation statements)
references
References 80 publications
11
107
2
2
Order By: Relevance
“…Genetic variations among three major East Asian subpopulations (Japanese, Korean and Chinese) have also been reported with respect to enzymes, including the CYP19*3 variant (Man et al, 2010), although variations are much smaller than between Europeans and Africans. However, there have been no reports regarding the genetic heterogeneity of enzymes involved in AA metabolism, and few studies have described the relationship between PFAA profiles and either ethnicity or subpopulations.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Genetic variations among three major East Asian subpopulations (Japanese, Korean and Chinese) have also been reported with respect to enzymes, including the CYP19*3 variant (Man et al, 2010), although variations are much smaller than between Europeans and Africans. However, there have been no reports regarding the genetic heterogeneity of enzymes involved in AA metabolism, and few studies have described the relationship between PFAA profiles and either ethnicity or subpopulations.…”
mentioning
confidence: 96%
“…It has been reported that the frequency of single nucleotide polymorphisms in certain enzymes involved in drug metabolism is associated with ethnicity (Man et al, 2010). Genetic variations among three major East Asian subpopulations (Japanese, Korean and Chinese) have also been reported with respect to enzymes, including the CYP19*3 variant (Man et al, 2010), although variations are much smaller than between Europeans and Africans.…”
mentioning
confidence: 99%
“…These include Brazil, 35 Iran, 36,37 East Asia, 38 Ghana, 39 United States Ashkenazi Jews, 40 Greece, 41 Mexican Americans, 42 Bolivia, 43 Israel, 44 Malaysia, 45 Egypt, 46 and whites of European descent. 47 However, these studies were limited to a small number of deficiency alleles and did not include the *17 gain-of-function allele.…”
mentioning
confidence: 99%
“…Recently, global clinical trials have been conducted throughout the globe in line with the guidelines of the ICH-GCP [1][2][3][4][5][6][7]. On the other hand, the inspection result from other Asian countries has not yet been accessible.…”
Section: Discussionmentioning
confidence: 99%
“…Recently global clinical trials have been conducted not only in developed countries but also in developing countries based on the International Conference on Harmonization of Technical Requirements for Registration of Pharmaceuticals for Human Use of Good Clinical Practice (ICH-GCP) guidelines [1][2][3][4][5][6][7]. To deliver the new, effective drugs to patients as rapid as possible, the guidelines have been playing the very important role to ensure the quality of clinical trials.…”
Section: Introductionmentioning
confidence: 99%